The relationship between mindfulness in parenting and parental stress among parents of adolescents - Georgie, Elizabeth Togot; Hassan, Siti Aishah; Rahman, Md. Mahfuzur; Kader, Romana (Human Resource Management Academic Research Society, 2023)
During this pandemic era, more challenging parenting experiences were observed. Adolescents either keep the problems to themselves or express through misbehaving with parents. This study aimed to examine the relationship between mindfulness in parenting and parental stress. A correlational study was conducted among parents of adolescents in Kuching District, Sarawak. Single - stage cluster sampling was used for recruiting 153 participants. Findings shows significant negative relationship between mindfulness in parenting and parental stress. In conclusion, mindfulness parenting seems to buffer parenting stress. Practically, parents need to be aware, reflect, understand, and seek treatment in order to improve self-care and assist their adolescents.